THE INFLUENCE OF ISLAM IN INDONESIAN FOREIGN POLICY: CASE STUDY ON ROHINGYA CONFLICT - Mohamad Zaidi bin Abdul Rahman; Akhmad Baihaqie (Universitas Islam Negeri Ar-Raniry, 2017)
This article attempts to argue that Islam, in its political activism, has arguably informed the shape of Indonesian foreign policy, especially during President Yudhoyono administration. In order to build the case, this research focuses on the Indonesia's responses towards the Rohingya conflict in Myanmar. Using state level analysis, which stresses on the supremacy of domestic analysis in understanding foreign policy, this article comes to the conclusion that domestic pressure, mainly from Muslim organizations, has directed Indonesia's response from abstention in dealing with the case to activism.